Medical tablets identification : mobile phone application development - Pang, Michelle Hui Qi (Nanyang Technological University, 2020)
In today’s society, health is a common recurring issue that is important. As more illnesses are identified, there is a need for more types of vaccines and medicines to counter them, increasing the variety of medicines available in the world. From pills with similar names, to pills with similar physical appearance, as well as pills that have the same usage but are of different dosages, it is very easy for patients to get confused (Health Behaviour News Service, 2013). This problem is further emphasized when the patient removes their medicine from their original packaging to place them in their own pill boxes for easy transportation (Basaraba, 2019), or, when the labels of pill bottles and pill pouches are damaged through wear and tear. With technology continuing to advance, it is now common for a person to own a smartphone, regardless of their age (The Guardian, 2020). Smartphones are evolving and constantly being equipped with new or updated features. These features can be used to help produce mobile applications that can be useful for society (CNN , 2014). Thus, the aim of this project is to develop a user-friendly mobile phone application that can record, store and process the images measured by the phone camera. In this project, the database for the storage and collection of the information of the medical tablets and the user interface of the mobile application has been developed.